Pengembangan Sistem Promosi Online Kain Tenun Khas Sipirok pada Usaha Tenun Anni Tupang Menggunakan OpenCart - Syahidah Tampubolon, Siti; Annas, Firdaus (JOVISHE : Journal of Visionary Sharia Economy, 2023)
Annie Tupang Weaving Business is one of the MSMEs producing Sipirok’s traditional woven fabrics with high cultural and aesthetic value. Each motif on the woven fabrics carries cultural significance derived from the 'abit godang' of South Tapanuli. In the digital era, this MSME faces challenges in promoting and marketing its products due to reliance on limited traditional methods, such as word-of-mouth marketing and basic social media use. These limitations result in reduced market reach and low promotional efficiency. This article aims to develop an online promotion system using the OpenCart platform as a digital solution to enhance competitiveness, expand market reach, and improve operational efficiency. The study adopts the Prototype Development Model (PPE), comprising three main stages: Planning, Development, and Evaluation. During the Planning stage, a needs analysis was conducted through interviews and observations of business processes. The Development stage included the installation and configuration of the OpenCart platform to meet system requirements. The Evaluation stage involved functional testing and user feedback. The results demonstrate that the OpenCart-based system provides effective features for managing product catalogs, online payments, order management, and transaction tracking. Furthermore, it reduces the costs of traditional promotions, such as brochure printing, and improves the consumer experience through more practical access. In conclusion, implementing an OpenCart-based e-commerce system using the PPE model can be a strategic step to support MSME development in the digital era, particularly in significantly enhancing the promotion of Sipirok’s traditional woven products.